2022
DOI: 10.5817/cp2022-3-9
|View full text |Cite
|
Sign up to set email alerts
|

The validation of the Perceived Surveillance Scale

Abstract: Data-driven practices, such as personalized communication, computational advertising, and algorithmic decision making, are now commonplace. However, they have been criticized for (mis)uses of personal data and invasions of people’s privacy. Recently, scholars have started to examine the concept of perceived surveillance to obtain more insight into the perceptions and effectiveness of data-driven communication. Despite the growing research interest in perceived surveillance, there is no validated scale to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…Prior work shows that in the case of behavioral advertising, persuasion knowledge affects privacy risk perceptions. While existing research shows that if people know that they are exposed to personalized messages, this affects privacy risks [54] or that users even feel that these messages are intrusive or creepy, our results did not align with this [23,53]. Moreover, we would like to point out that our result aligns with the novel work by Dobber and colleagues, who also did not find a relationship between exposure to transparency information and users' privacy concerns [36].…”
Section: Plos Onecontrasting
confidence: 93%
See 1 more Smart Citation
“…Prior work shows that in the case of behavioral advertising, persuasion knowledge affects privacy risk perceptions. While existing research shows that if people know that they are exposed to personalized messages, this affects privacy risks [54] or that users even feel that these messages are intrusive or creepy, our results did not align with this [23,53]. Moreover, we would like to point out that our result aligns with the novel work by Dobber and colleagues, who also did not find a relationship between exposure to transparency information and users' privacy concerns [36].…”
Section: Plos Onecontrasting
confidence: 93%
“…Other work shows that higher levels of personalization lead to higher perceived creepiness of advertisements [50]. Recent work validating a scale on perceived surveillance concerning personalization effects found that users experience creepiness, concerns about surveillance, perceptions of privacy risks overall, and privacy concerns [53]. In addition, other work found that in the case of data-driven OBA, persuasion knowledge, on which the concept of targeting knowledge is built, positively affects privacy risks, which could be considered as the cost side of the privacy calculus theory [54].…”
Section: Privacy Concernsmentioning
confidence: 99%
“…The scales used in the research are as follows: 1) Perceived personalization scale, (Srinivasan et al, 2002): 5 statements 2) Perceived surveillance scale (Segijn et al, 2022): 4 statements 3) Privacy concern scale (Baek & Morimoto, 2012): 6 statements 4) Brand usage intention scale (Yoo & Donthu, 2001;Hollebeek et al, 2014): 4 statements…”
mentioning
confidence: 99%